Spheroidal graphite cast iron member and manufacturing method of spheroidal graphite cast ion member
By controlling the volume ratios and thickness of the iron-nitrogen compound layer in spheroidal graphite cast iron through a two-stage nitriding process, the fatigue limit is enhanced, addressing the limitations of existing treatments.
Patent Information
- Application Number
- JP2023097040
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-25
AI Technical Summary
Spheroidal graphite cast iron subjected to nitriding treatment achieves a fatigue limit of about 90% of conventional materials, but further improvement is required, and the distribution of the γ' phase in the nitride layer is not adequately analyzed.
A spheroidal graphite cast iron member with a controlled iron-nitrogen compound layer thickness of 2 μm to 25 μm, where the volume ratio of the γ' phase to the total phases (γ'+ε+α) is 0.6 or more, and the α phase is 0.05 or less, is produced through a two-stage nitriding process at specific nitriding potentials.
The fatigue limit of the spheroidal graphite cast iron member is significantly improved, meeting practical requirements.
Smart Images

Figure 2024178700000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a spheroidal graphite cast iron member having excellent quietness. [Background technology]
[0002] Gears used in railway drive systems are required to be quiet so as not to cause excessive discomfort to passengers and residents living along the railway line.
[0003] According to Non-Patent Document 1, spheroidal graphite cast iron is expected to be a new material for railway gears because the graphite contained within it attenuates vibrations, resulting in excellent material damping properties (and therefore quietness). Non-Patent Document 1 also reports that nitriding-treated spheroidal graphite cast iron can achieve a fatigue limit of approximately 90% of that of conventional materials.
[0004] According to Non-Patent Document 2, the nitride layer of the nitrided material obtained by nitriding spheroidal graphite cast iron is composed of the γ' phase (Fe 4 It has been reported that N) is the main [Prior art documents] [Non-patent literature]
[0005] [Non-Patent Document 1] "Effect of nitriding treatment on fatigue strength properties of high-strength spheroidal graphite cast iron" by Akira Sugawara, Naoto Shiraki, Akihiko Nozaki, and Minoru Sasakura, published on September 1, 2019, Abstracts of the 173rd National Lecture Meeting of the Japan Foundry Engineering Society, p. 4 (Japan Foundry Engineering Society) [Non-Patent Document 2] "Effect of alloying elements on fatigue properties of nitrided ductile cast iron" Yusuke Kawasaki, Junichi Sumioka, Minoru Hatate, Nobuki Seki, Naoji Hamasaka, Yasufumi Yamaguchi, Published on January 25, 2015, Journal of the Japan Foundry Engineering Society, Casting Engineering, Vol. 87, No. 1, pp. 3-8 (Japan Foundry Engineering Society) Summary of the Invention [Problem to be solved by the invention]
[0006] As mentioned above, Non-Patent Document 1 reports that nitriding-treated spheroidal graphite cast iron can achieve a fatigue limit of approximately 90% of that of conventional materials, but further improvement in fatigue strength is desired.
[0007] As mentioned above, Non-Patent Document 2 also describes the γ' phase (Fe 4 It is stated that a nitride material having a nitride layer mainly composed of N was produced, but the details of the phase distribution of the nitride layer were not analyzed.
[0008] On the other hand, based on the results of verification of the examples and comparative examples described later, the inventors of the present invention have determined that, with respect to an iron-nitrogen compound layer obtained by nitriding spheroidal graphite cast iron, when the volume ratio of the γ' phase in the iron-nitrogen compound layer is Vaγ', the volume ratio of the ε phase in the iron-nitrogen compound layer is Vaε, and the volume ratio of the α phase in the iron-nitrogen compound layer is Vaα, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was found that the fatigue limit was significantly improved when all three conditions above were met.
[0009] Furthermore, the present inventors have discovered that the nitriding potential used in controlling the nitriding treatment for producing spheroidal graphite cast iron satisfying such conditions is slightly higher than the nitriding potential range that has been selected in nitriding treatment aimed at increasing the volume fraction of the γ' phase in general low-alloy steels.
[0010] The present invention has been made based on the above findings. An object of the present invention is to provide a spheroidal graphite cast iron member that is excellent in quietness and can realize a fatigue limit sufficient for practical use. [Means for solving the problem]
[0011] The present invention relates to A spheroidal graphite cast iron member having a spheroidal graphite cast iron base material and an iron-nitrogen compound layer formed on the surface side, The thickness of the iron-nitrogen compound layer is 2 μm to 25 μm, a volume ratio of a γ' phase in the iron-nitrogen compound layer being Vaγ', a volume ratio of an ε phase in the iron-nitrogen compound layer being Vaε, and a volume ratio of an α phase in the iron-nitrogen compound layer being Vaα, wherein a ratio of Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more and a ratio of Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It is.
[0012] According to the present invention, an iron-nitrogen compound layer having a thickness in the range of 2 μm to 25 μm is provided, and a γ' phase is formed in the iron-nitrogen compound layer such that the ratio defined by Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more and the ratio defined by Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less, thereby improving the fatigue limit of the spheroidal graphite cast iron member.
[0013] Vaγ' / (Vaγ'+Vaε+Vaα) and Vaα / (Vaγ'+Vaε+Vaα) can be evaluated from electron microscope photographs of the cross section of the iron-nitrogen compound layer, and the threshold values of 0.6 and 0.03 for these ratios were derived by comparing and examining the examples and comparative examples described below.
[0014] Here, the spheroidal graphite cast iron is generally C: 2.0 to 4.0% by mass Si: 1.6 to 3.7% by mass Mn: 0.1 to 2.0% by mass P: 0.08% or less in mass% S: 0.03% or less by mass Cu: 0.1 to 4.0% by mass Sn: 0.08% or less by mass%, and Mg: 0.02 to 0.1% by mass Contains:
[0015] The spheroidal graphite cast iron further comprises V: 0.05 to 0.6% by mass, and / or Mo: 0.7% or less by mass may also include
[0016] The spheroidal graphite cast iron further comprises Cr: 1.0% or less by mass%, and / or Al: 0.5% or less by mass may also include
[0017] Furthermore, the present inventors have found that the thickness of the iron-nitrogen compound layer is more preferably 7.5 μm to 25 μm.
[0018] Furthermore, the inventors of the present invention have found that the ratio defined by Vaγ' / (Vaγ'+Vaε+Vaα) is more preferably 0.8 or more.
[0019] The present invention also provides a method for producing a semiconductor device comprising the steps of: A method for manufacturing a spheroidal graphite cast iron member, comprising: A nitriding process in which spheroidal graphite cast iron is gas-nitrided in a nitriding gas atmosphere of the first nitriding potential in a furnace at 500℃ to 600℃. Equipped with The first nitriding potential is 0.5 to 3.0. The present invention relates to a method for producing a spheroidal graphite cast iron member.
[0020] The inventors have thus determined that a ductile iron component that satisfies the above-mentioned parameter conditions can be manufactured using a relatively high nitriding potential.
[0021] The present invention also provides a method for producing a semiconductor device comprising the steps of: A method for manufacturing a spheroidal graphite cast iron member comprising at least two nitriding treatment steps, A first nitriding process step of nitriding the spheroidal graphite cast iron member in a nitriding gas atmosphere having a first nitriding potential; A second nitriding process step of further nitriding the spheroidal graphite cast iron member in a nitriding gas atmosphere having a second nitriding potential lower than the first nitriding potential after the first nitriding process step, The first nitriding step is carried out at a temperature of 500°C to 600°C, The second nitriding step is also carried out at a temperature of 500°C to 600°C, the second nitriding potential is a value within a range of 0.5 to 3.0; The duration of the first nitriding step is longer than the duration of the second nitriding step. A method for manufacturing a spheroidal graphite cast iron member, comprising: It is.
[0022] The inventors have thus determined that a ductile iron component that satisfies the above-mentioned parameter conditions can be manufactured using a relatively high nitriding potential. Effect of the Invention
[0023] According to one embodiment of the present invention, an iron-nitrogen compound layer having a thickness in the range of 2 μm to 25 μm is provided, and a γ' phase is formed in the iron-nitrogen compound layer such that the ratio defined by Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more and the ratio defined by Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less, thereby improving the fatigue limit of the spheroidal graphite cast iron member.
[0024] In accordance with another aspect of the present invention, a relatively high nitriding potential may be used to produce ductile iron components that meet the parameter requirements set forth above. [Brief description of the drawings]
[0025] [Figure 1] 1 is a schematic diagram showing the configuration of a pit-type (single-chamber) heat treatment furnace used in a method for producing a spheroidal graphite cast iron member according to an embodiment of the present invention. [Diagram 2] 2 is a process diagram of one embodiment of a nitriding method that can be employed in the heat treatment furnace of FIG. 1. [Diagram 3]FIG. 1 is a schematic diagram of a batch-type heat treatment furnace used in a method for producing a spheroidal graphite cast iron member according to an embodiment of the present invention. [Figure 4] 4 is a process diagram of one embodiment of a nitriding method that can be used in the heat treatment furnace of FIG. 3. [Diagram 5] 1 is a cross-sectional optical microscope photograph of a spheroidal graphite cast iron member according to an embodiment of the present invention. [Figure 6] 1 is a table showing base material components of each example of the present invention. [Figure 7] 1 is a table showing nitriding conditions, post-nitriding characteristics, and fatigue test results for each example of the present invention. [Figure 8] 1 is a table showing base material components of each comparative example. [Figure 9] 1 is a table showing nitriding conditions, post-nitriding characteristics, and fatigue test results for each comparative example. [Figure 10] FIG. 2 is a diagram showing the shape of an Ono-type rotating bending fatigue test piece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Preferred embodiments of the present invention will be described below, but the present invention is not limited to the following embodiments.
[0027] [Workpiece] The workpiece is made of spheroidal graphite cast iron. The spheroidal graphite cast iron member after nitriding is expected to be used for gears in railway drive devices, etc., but in this embodiment, the workpiece is made into a bar shape as shown in Fig. 10 for the fatigue limit evaluation test.
[0028] It is preferable that the workpiece be pre-cleaned to remove dirt and oil before the nitriding process. Pre-cleaning is preferably performed by, for example, vacuum cleaning, which dissolves and replaces oil and the like in a hydrocarbon-based cleaning liquid and evaporates it to degrease and dry, or alkaline cleaning, which degreases the workpiece with an alkaline cleaning liquid.
[0029] [Example of the configuration of a pit-type heat treatment furnace] FIG. 1 is a schematic diagram showing the configuration of a pit-type heat treatment furnace 5 used in the method for producing a spheroidal graphite cast iron member of the present invention.
[0030] As shown in FIG. 1, a pit-type heat treatment furnace 5 includes a bottomed cylindrical furnace wall 6 and a furnace lid 7.
[0031] A fan 8 is provided below (inside) the furnace lid 7, and the rotating shaft of the fan 8 passes through the furnace lid 7 and is connected to a fan motor 9 provided above (outside) the furnace lid 7.
[0032] A retort 10 is provided inside the furnace wall 6, and a gas guide tube 11 is provided further inside the retort 10. The outer periphery of the retort 10 is heated by a heater (not shown), so that the temperature inside the furnace (inside the retort 10) is controlled to a predetermined temperature. A case 12 is placed inside the gas guide tube 11, and spheroidal graphite cast iron is stored in the case 12 as the object to be treated (work). The maximum treatment weight is 700 kg gross.
[0033] In addition, multiple types of gases for the nitriding treatment are introduced into the retort 10 under controlled conditions as described below. Furthermore, the outer periphery of the retort 10 also has a cooling function using a blower (not shown), and during cooling, the workpieces in the furnace are cooled by lowering the temperature of the retort 10 itself (furnace cooling).
[0034] [Example of operation of a pit-type heat treatment furnace] In the heat treatment furnace 5 configured as above, the furnace lid 7 is opened, and the case 12 containing the spheroidal graphite cast iron is carried into the gas guide tube 11. Then, after the spheroidal graphite cast iron (the case 12 containing the spheroidal graphite cast iron) is carried into the gas guide tube 11, a treatment gas is introduced into the gas guide tube 11, the treatment gas is heated to a predetermined temperature by a heater, and further, while being stirred by a fan 8 (rotating at, for example, 1500 rpm), the nitriding treatment of the spheroidal graphite cast iron member carried into the gas guide tube 11 is performed.
[0035] FIG. 2 is a process diagram of one embodiment of a nitriding method that can be employed in the heat treatment furnace 5 of FIG.
[0036] In the example of FIG. 2, spheroidal graphite cast iron (workpiece) is loaded into the gas guide tube 11, and then the inside of the retort 10 is heated to 550° C. In the first half of this heating process (heating (1) process), N 2 Gas was introduced at a constant flow rate of 40 (L / min), and NH 3 Gas and AX gas are introduced at a constant flow rate of 40 (L / min).
[0037] Thereafter, a two-stage nitriding process is carried out. Specifically, a value of, for example, 1.5 is adopted as the first nitriding potential, and the first nitriding process is carried out at a temperature of 550°C.
[0038] Nitriding potential K N NH 3 Partial pressure of gas P(NH 3 ) and H 2 Partial pressure of gas P(H 2 ) is known to be expressed by the following formula: K N = P(NH 3 ) / P(H 2 ) 3 / 2
[0039] In the first nitriding process, for example, a thermoelectric H 2 Via the sensor 13 (see FIG. 1), NH 3 Partial pressure of gas P(NH 3 ) or H 2 Partial pressure of gas P(H 2 ) is measured, and the amount of the process gas introduced is feedback-controlled so that the value of the nitriding potential calculated from the measured value falls within a range close to the target first nitriding potential. The feedback control is, for example, N The regulator controls the flow rate of each process gas via a gas flow regulator MFC14 provided in the introduction path of each process gas.
[0040] In the example in Figure 2, H in the exhaust gas 2 Partial pressure of gas P(H 2 ) is H in the thermal conductivity formula 2 The amount of the process gas introduced is feedback-controlled while the measured value is analyzed online (the nitriding potential is calculated from the measured value). Specifically, AX gas is introduced at a constant flow rate of 20 (L / min), while NH 3 The gas is increased or decreased, and the total flow rate also changes.
[0041] In the example of Fig. 2, such a first nitriding treatment step is carried out for 240 minutes, whereby an iron-nitrogen compound layer mainly consisting of a γ' phase, an ε phase, or a mixture of a γ' phase and an ε phase is formed in the spheroidal graphite cast iron member.
[0042] Subsequently, a second nitriding potential of, for example, 0.6 is adopted, and a second nitriding process is carried out at a temperature of 550°C.
[0043] In the second nitriding process, for example, a thermoelectric H 2 Via the sensor 13 (see FIG. 1), NH 3 Partial pressure of gas P(NH 3 ) or H 2 Partial pressure of gas P(H 2 ) is measured, and the amount of the process gas introduced is feedback-controlled so that the value of the nitriding potential calculated from the measured value falls within a range near the target second nitriding potential.
[0044] In the example in Figure 2, H in the exhaust gas 2 Partial pressure of gas P(H 2 ) is H in the thermal conductivity formula 2 The amount of the process gas introduced is feedback-controlled while the measured value is analyzed online (the nitriding potential is calculated from the measured value). Specifically, AX gas is introduced at a constant flow rate of 30 (L / min), while NH 3 The gas is increased or decreased, and the total flow rate also changes.
[0045] In the example of Fig. 2, such a second nitriding step is carried out for 60 minutes, whereby mainly the γ' phase is precipitated in the iron-nitride compound layer.
[0046] After the second nitriding process is completed, a cooling process is performed. In the example of FIG. 2, in the first half of the cooling process (to about 400°C: cooling (1) process), the amount of processing gas introduced is controlled in the same manner as in the second nitriding process. That is, AX gas is introduced at a constant flow rate of 30 (L / min), while NH 3 The amount of gas is increased or decreased. In the latter half of the cooling process (400℃ to 100℃: cooling (2) process), N 2 Gas is introduced at a constant flow rate of 20 (L / min). When the cooling process is completed, the furnace cover 7 is opened, and the case 12 containing the spheroidal graphite cast iron member is carried out from the gas guide tube 11.
[0047] [Example of the configuration of a batch-type heat treatment furnace] FIG. 3 is a schematic diagram showing the configuration of a batch-type heat treatment furnace 15 used in the method for producing a spheroidal graphite cast iron member of the present invention.
[0048] As shown in Fig. 3, the batch-type heat treatment furnace 15 includes a carry-in section 16, a heating chamber 17, a transport chamber 18, and an unloading section 19. A case 20 is placed in the carry-in section 16, and a spheroidal graphite cast iron member as a workpiece is stored in the case 20. The maximum processing weight is 700 kg gross.
[0049] An openable and closable door 21 is attached to the entrance side (right side in FIG. 3) of the heating chamber 17. The heating chamber 17 has a retort structure, and the temperature inside the furnace is controlled to a predetermined temperature by heating the outer periphery of the retort with a heater (not shown). A plurality of types of gases for nitriding treatment are introduced into the heating chamber 17 while being controlled as described below.
[0050] A fan 22 is attached to the ceiling of the heating chamber 17 to uniformly heat the spheroidal graphite cast iron by stirring the gas introduced into the heating chamber 17. A middle door 23 that can be opened and closed freely is attached to the outlet side of the heating chamber 17 (the left side in FIG. 4).
[0051] The transfer chamber 18 is provided with an elevator (details not shown) for raising and lowering a case 20 in which spheroidal graphite cast iron is stored. A cooling chamber (oil tank) 24 that stores oil for cooling is provided in the lower part of the transfer chamber 18, and an agitator 25 for agitating the oil is attached. A door 26 that can be opened and closed freely is attached to the exit side of the transfer chamber 18 (left side in FIG. 4).
[0052] The heating chamber 17 and the transfer chamber 18 may be formed as a processing chamber in the same space, and the spheroidal graphite cast iron member after the nitriding treatment may be air-cooled by gas. Also, the heating chamber 17 may be divided into two, and the two-stage nitriding treatment process described later may be performed in each heating chamber.
[0053] [Example of operation of a batch-type heat treatment furnace] In the heat treatment furnace 15 configured as above, the case 20 containing the spheroidal graphite cast iron is carried into the heating chamber 17 from the carrying-in section 16 by a pusher or the like. Then, after the spheroidal graphite cast iron member (the case 20 containing the spheroidal graphite cast iron member) is carried into the heating chamber 17, a treatment gas is introduced into the heating chamber 17, the treatment gas is heated to a predetermined temperature by a heater, and the spheroidal graphite cast iron carried into the heating chamber 17 is nitrided while being stirred by a fan 22 (rotating at, for example, 1500 rpm).
[0054] FIG. 4 is a process diagram of one embodiment of a nitriding method that can be employed in the heat treatment furnace 15 of FIG.
[0055] In the example of FIG. 4, before the spheroidal graphite cast iron (workpiece) is charged, the inside of the heating chamber 17 is preheated to 550° C. During this heating process, N 2 Gas was introduced at a constant flow rate of 70 (L / min), and NH 3Gas is introduced at a constant flow rate of 90 (L / min). The total flow rate is 70 (L / min) + 90 (L / min) = 160 (L / min).
[0056] Next, spheroidal graphite cast iron (workpiece) is loaded into the heating chamber 17. At this time, the door 21 is opened, and the temperature inside the heating chamber 17 temporarily drops, as shown in Fig. 4. After that, the door 21 is closed, and the temperature inside the heating chamber 17 is heated again to 550°C.
[0057] Even during the charging of such spheroidal graphite cast iron components, in the example shown in Figure 4, N 2 Gas was introduced at a constant flow rate of 70 (L / min), and NH 3 Gas is introduced at a constant flow rate of 90 (L / min), and the total flow rate is 70 (L / min) + 90 (L / min) = 160 (L / min).
[0058] Thereafter, a two-stage nitriding process is carried out. Specifically, a value of, for example, 1.5 is adopted as the first nitriding potential, and the first nitriding process is carried out at a temperature of 550°C.
[0059] As mentioned above, the nitriding potential K N NH 3 Partial pressure of gas P(NH 3 ) and H 2 Partial pressure of gas P(H 2 ) is known to be expressed by the following formula: K N = P(NH 3 ) / P(H 2 ) 3 / 2
[0060] In the first nitriding process, for example, a thermoelectric H 2 Via the sensor 27 (see FIG. 3), the NH 3 Partial pressure of gas P(NH 3 ) or H 2 Partial pressure of gas P(H 2) is measured, and the amount of the process gas introduced is feedback-controlled so that the value of the nitriding potential calculated from the measured value falls within a range close to the target first nitriding potential. The feedback control is, for example, N The regulator controls the flow rate of each process gas via a gas flow regulator MFC 28 provided in the introduction path of each process gas.
[0061] In the example of FIG. 4, H 2 Partial pressure of gas P(H 2 ) is H in the thermal conductivity formula 2 The amount of the process gas introduced is feedback-controlled while the measured value is analyzed online (while the nitriding potential is calculated from the measured value). 2 Gas was introduced at a constant flow rate of 70 (L / min), while NH 3 The flow rates of the AX gas and the AX gas are increased or decreased under the condition that the total flow rate is 90 (L / min). The total flow rate is maintained at 70 (L / min) + 90 (L / min) = 160 (L / min).
[0062] In the example of Fig. 4, such a first nitriding treatment step is carried out for 240 minutes, whereby an iron-nitrogen compound layer mainly consisting of a γ' phase, an ε phase, or a mixture of a γ' phase and an ε phase is formed in the spheroidal graphite cast iron member.
[0063] Subsequently, a second nitriding potential of, for example, 0.6 is adopted, and a second nitriding process is carried out at a temperature of 550°C.
[0064] In the second nitriding process, for example, a thermoelectric H 2 Via the sensor 27 (see FIG. 3), the NH 3 Partial pressure of gas P(NH 3 ) or H 2 Partial pressure of gas P(H 2 ) is measured, and the amount of the process gas introduced is feedback-controlled so that the value of the nitriding potential calculated from the measured value falls within a range near the target second nitriding potential.
[0065] In the example of FIG. 4, H 2 Partial pressure of gas P(H 2 ) is H in the thermal conductivity formula 2 The amount of the process gas introduced is feedback-controlled while the measured value is analyzed online (while the nitriding potential is calculated from the measured value). 3 The flow rates of the gas and the AX gas are increased or decreased under the condition that the total flow rate is 160 (L / min).
[0066] In the example of Fig. 2, such a second nitriding step is carried out for 60 minutes, whereby mainly the γ' phase is precipitated in the iron-nitride compound layer.
[0067] When the second nitriding process is completed, a cooling process is performed. In the example of Fig. 4, the cooling process is performed for 15 minutes (in an oil tank equipped with an agitator, the material is kept in oil (100°C) for 15 minutes). When the cooling process is completed, the case 20 containing the spheroidal graphite cast iron member for which the nitriding process has been completed is carried out to a carrying-out section 19 (e.g., a carrying-out conveyor).
[0068] [Cross-sectional micrograph of one embodiment of a spheroidal graphite cast iron member] Fig. 5 is a cross-sectional micrograph of a spheroidal graphite cast iron member 1 according to one embodiment of the present invention. As shown in Fig. 5, the spheroidal graphite cast iron member 1 according to this embodiment has an iron-nitrogen compound layer 2 formed on the surface thereof, and below the iron-nitrogen compound layer 2, a diffusion layer 3 in which nitrogen is diffused into the matrix is provided.
[0069] 5, the iron nitrogen compound layer 2 has a thickness of 10 to 15 μm. The diffusion layer 3 exists directly below the iron nitrogen compound layer 2 to a depth of about 250 μm, and has a hardness of 500 HV to 700 HV.
[0070] The parent phase (base material) of the spheroidal graphite cast iron member 1 is spheroidal graphite cast iron, and spheroidal graphite 4 is found inside the parent phase. A fatigue test piece shown in FIG. 10 was manufactured from the spheroidal graphite cast iron, and the above-mentioned nitriding treatment (FIG. 2 or FIG. 4) was performed on this fatigue test piece to obtain the spheroidal graphite cast iron member 1.
[0071] [Details of Examples and Comparative Examples] Examples of the present invention and comparative examples will be specifically described below, although the present invention is not limited to these examples.
[0072] 6 is a table showing the steel composition of the base material (spheroidal graphite cast iron) of each of Examples 1-1 to 1-27, with the balance being iron (Fe) and unavoidable impurities. In addition, "---" in the table indicates that no addition was made or that the amount was so small that quantitative analysis was not possible.
[0073] 7 is a table showing the steel composition of the base material (spheroidal graphite cast iron) of each of Comparative Examples 1-1 to 1-10, with the balance being iron (Fe). The steel composition of the base material (spheroidal graphite cast iron) of each of Comparative Examples 1-1 to 1-10 is the same as the steel composition of the base material (spheroidal graphite cast iron) of each of Examples 1-1 to 1-10.
[0074] Below, the general knowledge of those skilled in the art regarding each component will be explained.
[0075] C (carbon) is an important element that affects the amount of spheroidal graphite crystallized, the amount of lamellar cementite in pearlite, the amount of MC carbide precipitated, and the fluidity and white iron of the molten iron. If the C content is less than 2.0%, the amount of graphite is insufficient, white iron is promoted, and the fluidity is insufficient, making it difficult to obtain spheroidal graphite cast iron that ensures the desired high strength and high ductility. On the other hand, if the C content exceeds 4.0%, the amount of graphite becomes excessive, and the strength decreases. For this reason, the C content is preferably 2.0% to 4.0%.
[0076] Silicon (Si) is an element that affects the fluidity and whitening of molten metal. If the Si content is less than 1.6%, the fluidity decreases, making it difficult to fill the molten metal into the thin wall and whitening also occurs. On the other hand, if the Si content exceeds 3.7%, ferrite is likely to precipitate in the matrix, making it difficult to achieve high strength. For this reason, the Si content is preferably 1.6% to 3.7%.
[0077] Mn (manganese) is an element that is inevitably mixed in from the raw material, but it is an element that stabilizes the pearlite structure and has the effect of precipitating the pearlite structure. In order to obtain such an effect sufficiently while ensuring a predetermined hardness, the Mn content is preferably at least 0.1%. If the Mn content is 2.0% or less, the machinability and toughness of the spheroidal graphite cast iron are improved. On the other hand, if the Mn content exceeds 2.0%, the structure of the cast iron tends to become chilled. Therefore, the Mn content is preferably 0.1% to 2.0%.
[0078] P (phosphorus) is an element that increases porosity and segregates at the grain boundaries of solidification cells, embrittling the material; it is a so-called impurity. Therefore, it is desirable to reduce it as much as possible. If the P content exceeds 0.08%, the above-mentioned adverse effects become significant. In other words, the P content is preferably 0.08% or less. (There is no particular lower limit, but it is unnecessary and uneconomical to reduce it to below the detection limit, for example. In this sense, the lower limit can be said to be about 0.005%.)
[0079] S (sulfur) is an element that is inevitably mixed in from the raw material, but is an element that inhibits the spheroidization of graphite, and if the S content exceeds 0.03%, the spheroidization of graphite is reduced. On the other hand, if the S content is less than 0.005%, the amount of sulfides that serve as nuclei when spheroidal graphite crystallizes decreases, the amount of crystallized spheroidal graphite decreases, and the spheroidization rate decreases. Therefore, the S content is preferably 0.005% to 0.03%.
[0080] Cu (copper) has the effect of densifying the pearlite structure and finely precipitating in the matrix to increase the strength of the matrix. In order to obtain such an effect sufficiently while securing a predetermined hardness, the Cu content is preferably at least 0.1%. On the other hand, if the Cu content exceeds 4.0%, a large amount of Cu segregates at the grain boundaries of the solidification cells, resulting in a decrease in strength. Therefore, the Cu content is preferably 0.1% to 4.0%.
[0081] Sn (tin) not only densifies the pearlite structure, but also prevents the spheroidization inhibition caused by the addition of Cu, and promotes high strength through a synergistic effect with Cu. On the other hand, if the Sn content exceeds 0.08%, the embrittlement effect becomes strong and the strength is significantly reduced. Therefore, the Sn content is preferably 0.08% or less.
[0082] Magnesium (Mg) has the effect of spheroidizing graphite and is an essential element in spheroidal graphite cast iron. To obtain such an effect, the Mg content must be 0.02% or more. On the other hand, if the Mg content exceeds 0.1%, Mg oxide generates a large amount of dross and increases surface defects. Therefore, the Mg content is preferably 0.02% to 0.1%.
[0083] Cr (chromium) is a carbide-forming element that suppresses the precipitation of ferrite and promotes and encourages the precipitation of pearlite, thereby improving mechanical properties. On the other hand, if the amount of Cr added exceeds 1.0%, chilling is promoted. Therefore, the Cr content is preferably 1.0% or less.
[0084] Mo (molybdenum), like Cr, densifies pearlite and improves mechanical properties. On the other hand, if the Mo content exceeds 0.7%, Mo and C combine to form carbides, which increases hardness and reduces ductility. Therefore, the Mo content is preferably 0.7% or less.
[0085] V (vanadium) is an element that improves tensile strength and yield strength at high temperatures by precipitating as fine carbides in the matrix. To obtain such an effect, the V content must be 0.05% or more. On the other hand, if the V content exceeds 0.6%, not only does it impair the ductility of cast iron, but it also has a strong tendency to form carbides, which hinders the spheroidization of graphite. Therefore, the V content is preferably 0.05% to 0.6%.
[0086] Aluminum (Al) is an element that promotes graphitization and has the effect of improving oxidation resistance, but if the Al content exceeds 0.5%, castability deteriorates, so the Al content is preferably 0.5% or less.
[0087] The present inventors obtained spheroidal graphite cast iron members by subjecting notched test pieces having the shape shown in Fig. 10, which are made of various spheroidal graphite cast irons shown in Fig. 6 and Fig. 7 as examples of the present invention or comparative examples of the present invention to various nitriding treatments shown in Fig. 8 and Fig. 9. Then, the thickness of the iron-nitrogen compound layer, Vaγ' / (Vaγ'+Vaε+Vaα), Vaα / (Vaγ'+Vaε+Vaα), and fatigue properties of these spheroidal graphite cast iron members were evaluated.
[0088] (1) Thickness of the iron-nitride layer The thickness of the iron-nitrogen compound layer 2 was evaluated by cutting the nitrided spheroidal graphite cast iron member 1 in the depth direction and using a micrograph of the cross section. Specifically, a 100 μm×100 μm region including the outermost surface was defined as one visual field, and the thickness was evaluated based on the average value of five visual fields.
[0089] (2) Vaγ' / (Vaγ'+Vaε+Vaα) (3) Vaα / (Vaγ'+Vaε+Vaα) The phase structure was analyzed by cutting the nitrided spheroidal graphite cast iron member 1 in the depth direction, mechanically mirror-polishing the cross section, and then obtaining a "Phase Map" (analysis diagram) using an electron backscatter diffraction (EBSD) device (Inca Crystal, manufactured by Oxford Instruments) attached to a scanning electron microscope (Sirion, manufactured by FEI) (EES measurement). From this "Phase Map", Vaγ' / (Vaγ'+Vaε+Vaα) and Vaα / (Vaγ'+Vaε+Vaα) can be obtained by a known image analysis method. Specifically, depending on the thickness of the iron-nitrogen compound layer 2, for example, a 600 μm area having a depth of 20 μm and a width of 30 μm from the outermost surface of the spheroidal graphite cast iron member 1 was obtained. 2 EBSD measurement is performed on the above and a "Phase Map" is created to distinguish between the γ', ε, and α phases. Then, for the obtained "Phase Map," an image analysis application is used to obtain Vaγ' / (Vaγ'+Vaε+Vaα) and Vaα / (Vaγ'+Vaε+Vaα). In the EBSD measurement, 10 fields of view are measured at a magnification of around 3000 times depending on the thickness of the iron-nitrogen compound layer 2, and the measurements are averaged.
[0090] (4) Fatigue properties The fatigue properties were evaluated by the Ono type rotating bending fatigue test (JIS Z 2274). Specifically, an Ono type rotating bending fatigue tester (Shimadzu Corporation, H7 type) was used, and the test load was set to a nominal stress of 470 MPa and a nominal stress of 517 MPa, and the rotation speed was set to 3000 rpm. The test results were evaluated after 10 7 Those that rotated were deemed good (indicated with a "○"), and then further tested for 10 7 The one that rotated was the best (indicated with "◎"), and the test was performed at a nominal stress of 470 MPa for 10 7 Those that broke within less than a revolution were deemed defective (indicated with "X").
[0091] (The heat treatment furnace and nitriding process used) 8 and 9 show the heat treatment furnace used and the nitriding conditions of the nitriding process for each of the examples and comparative examples.
[0092] The "pit type" corresponds to the heat treatment furnace 5 described with reference to FIGS. 1 and 2, and the "batch type" corresponds to the heat treatment furnace 15 described with reference to FIGS.
[0093] "K N The "K 1" column indicates the (target) first nitriding potential value of the first nitriding process, and the "Time" column to the right of it indicates the processing time of the first nitriding process. N The column "2" indicates the value of the (target) second nitriding potential in the second nitriding treatment step, and the column "Time" to the right of it indicates the treatment time of the second nitriding treatment step.
[0094] "K M When "-" is entered in the "2" column and the "Time" column to the right of it, this means that the second nitriding treatment step was not carried out, and only the first nitriding treatment step was carried out.
[0095] In Comparative Example 2-2, "No control" means that feedback control is not performed and NH 3This means that the flow rates of the AX gas and the AX gas were kept constant.
[0096] 8 and 9 show the thickness of the iron-nitrogen compound layer, Vaγ' / (Vaγ'+Vaε+Vaα), Vaα / (Vaγ'+Vaε+Vaα), and fatigue properties for each of the examples and comparative examples.
[0097] (C, Si, Mn, P, S, Cu, Mg, Sn) Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-4 shown in Figs. 8 and 9 belong to a group having C, Si, Mn, P, S, Cu, Mg, and Sn as base material components.
[0098] From the results of Examples 1-1 to 1-5 / Comparative Examples 1-1 to 1-4, in the group, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0099] (C, Si, Mn, P, S, Cu, Mg, Sn, Cr, Al) Examples 2-1 to 2-10 and Comparative Examples 2-1 to 2-3 shown in Figs. 8 and 9 belong to a group having C, Si, Mn, P, S, Cu, Mg, Sn, Cr, and Al as base material components.
[0100] From the results of Examples 2-1 to 2-10 / Comparative Examples 2-1 to 2-3, it was found that in this group, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0101] (C, Si, Mn, P, S, Cu, Mg, Sn, V) Examples 3-1 to 3-4 and Comparative Examples 3-1 to 3-3 shown in Figs. 8 and 9 belong to a group having C, Si, Mn, P, S, Cu, Mg, Sn, and V as base material components.
[0102] From the results of Examples 3-1 to 3-4 and Comparative Examples 3-1 to 3-3, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0103] (C, Si, Mn, P, S, Cu, Mg, Sn, Mo) Examples 4-1 to 4-3 shown in FIG. 8 belong to a group having C, Si, Mn, P, S, Cu, Mg, Sn, and Mo as base material components.
[0104] From the results of Examples 4-1 to 4-3, in this group, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0105] (C, Si, Mn, P, S, Cu, Mg, Sn, V, Mo) Example 5 shown in FIG. 8 has C, Si, Mn, P, S, Cu, Mg, Sn, V, and Mo as base material components.
[0106] From the results of Example 5, in this case as well, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0107] (C, Si, Mn, P, S, Cu, Mg, Sn, V, Cr) Example 6 shown in FIG. 8 has base material components of C, Si, Mn, P, S, Cu, Mg, Sn, V, and Cr.
[0108] From the results of Example 6, in this case too, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0109] (C, Si, Mn, P, S, Cu, Mg, Sn, V, Cr, Al) Example 7 and Example 8 shown in FIG. 8 have C, Si, Mn, P, S, Cu, Mg, Sn, V, Cr, and Al as base material components.
[0110] From the results of Examples 7 and 8, in this case as well, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0111] (C, Si, Mn, P, S, Cu, Mg, Sn, V, Al) Example 9 shown in FIG. 8 has base material components of C, Si, Mn, P, S, Cu, Mg, Sn, V, and Al.
[0112] From the results of Example 9, in this case as well, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. (3) The ratio Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. It was confirmed that the fatigue limit is significantly improved when all three conditions above are met.
[0113] (More favorable conditions) From the results of Example 1-3, Example 1-5, Example 2-2, Example 2-3, Example 2-5, Example 3-2, Example 3-4, Example 5, Example 8, and Example 9, (1) The thickness of the iron-nitride layer is 2 μm to 25 μm. The condition is preferably: (1') The thickness of the iron-nitrogen compound layer is 7.5 μm to 25 μm. and more preferably (1") The thickness of the iron-nitrogen compound layer is 10μm to 25μm. It can be said that, (2) The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more. The condition is preferably: (2') The ratio Vaγ' / (Vaγ'+Vaε+Vaα) is 0.8 or more. It can be said that it is.
[0114] (Additional information on base material components) According to the composition of each example, the present invention relates to the composition of the spheroidal graphite cast iron, which is the base material. C: 2.0 to 4.0% by mass Si: 1.6 to 3.7% by mass Mn: 0.1 to 2.0% by mass P: 0.08% or less in mass% S: 0.03% or less by mass Cu: 0.1 to 4.0% by mass Sn: 0.08% or less by mass%, and Mg: 0.02 to 0.1% by mass It can be seen that the range of application is inclusive of the above.
[0115] Spheroidal graphite cast iron is further V: 0.05 to 0.6% by mass, and / or Mo: 0.7% or less by mass It can be seen that the present invention is also applicable to cases including
[0116] Spheroidal graphite cast iron is further Cr: 1.0% or less by mass%, and / or Al: 0.5% or less by mass It can be seen that the present invention is also applicable to cases including
[0117] (Additional information about the nitriding process) From the results of each example, it can be seen that when only a single nitriding treatment step is carried out, it is preferable that spheroidal graphite cast iron is nitrided by a nitriding treatment step in a nitriding gas atmosphere having a first nitriding potential in the range of 0.5 to 3.0 in a furnace at 500°C to 600°C.
[0118] Furthermore, from the results of each example, it can be seen that when a two-stage nitriding process is carried out, after a first nitriding process in a furnace at 500°C to 600°C, the spheroidal graphite cast iron is preferably nitrided by a second nitriding process in a nitriding gas atmosphere having a second nitriding potential in the range of 0.5 to 3.0, which is lower than the first nitriding potential, in a furnace at 500°C to 600°C, and which lasts for a shorter period of time than the first nitriding process.
[0119] In more detail, Comparative Example 1-1 is the first nitriding potential (K M 1) was thought to be too low, Comparative Example 1-2 is the second nitriding potential (K M 2) was thought to be too low, Comparative Example 1-3 is the second nitriding potential (K M 2) was thought to be too high, Comparative Example 1-4 is the second nitriding potential (K M 2) was thought to be too low, Comparative Example 2-1 is the first nitriding potential (K M 1) was thought to be too high, In Comparative Example 2-2, feedback control was considered necessary. Comparative Example 2-3 is the second nitriding potential (K M 2) was thought to be too high, Comparative Example 3-1 is the first nitriding potential (K M 1) was thought to be too high, Comparative Example 3-2 is the second nitriding potential (K M 2) was thought to be too low, Comparative Example 3-3 is a second nitriding potential (K M 2) was probably too high. [Explanation of symbols]
[0120] 1 Spheroidal graphite cast iron components 2. Iron-nitride layer 3. Diffusion Layer 4. Spherical graphite 5. Heat treatment furnace 6 Furnace wall 7 Hearth cover 8 Fans 9. Fan motor 10 Retort 11 Gas guide tube 12 cases 13H 2 Sensors 14 Gas flow controller MFC 15 Heat treatment furnace 16 Loading section 17 Heating chamber 18 Transport Room 19 Unloading section 20 cases 21 Door 22 Fan 23 Middle Door 25 Mixer 26 Door 27H 2 Sensors 28 Gas flow controller MFC
Claims
1. A spheroidal graphite cast iron member having a spheroidal graphite cast iron base material and an iron-nitrogen compound layer formed on the surface side, The thickness of the iron-nitrogen compound layer is 2 μm to 25 μm, When a volume ratio of the γ' phase in the iron nitrogen compound layer is Vaγ', a volume ratio of the ε phase in the iron nitrogen compound layer is Vaε, and a volume ratio of the α phase in the iron nitrogen compound layer is Vaα, a ratio defined by Vaγ' / (Vaγ'+Vaε+Vaα) is 0.6 or more, and a ratio defined by Vaα / (Vaγ'+Vaε+Vaα) is 0.05 or less. A spheroidal graphite cast iron member characterized by:
2. The spheroidal graphite cast iron is C: 2.0 to 4.0% by mass Si: 1.6 to 3.7% by mass Mn: 0.1 to 2.0% by mass P: 0.08% or less in mass% S: 0.03% or less by mass Cu: 0.1 to 4.0% by mass Sn: 0.08% or less by mass%, and Mg: 0.02 to 0.1% by mass The ductile iron component according to claim 1, further comprising:
3. The spheroidal graphite cast iron further comprises V: 0.05 to 0.6% by mass, and / or Mo: 0.7% or less by mass Contains The spheroidal graphite cast iron member according to claim 2 .
4. The spheroidal graphite cast iron further comprises Cr: 1.0% or less by mass%, and / or Al: 0.5% or less by mass Contains The spheroidal graphite cast iron member according to claim 2 .
5. The thickness of the iron-nitrogen compound layer is 7.5 μm to 25 μm.
5. The nitrided steel member according to claim 1 .
6. The ratio defined by Vaγ' / (Vaγ'+Vaε+Vaα) is 0.8 or more. The spheroidal graphite cast iron member according to claim 5 .
7. A method for manufacturing a spheroidal graphite cast iron member, comprising: The method includes a nitriding step of gas-nitriding spheroidal graphite cast iron in a nitriding gas atmosphere having a first nitriding potential in a furnace at 500°C to 600°C, The first nitriding potential is 0.5 to 3.
0. A method for producing a spheroidal graphite cast iron member comprising the steps of:
8. A method for manufacturing a spheroidal graphite cast iron member comprising at least two nitriding treatment steps, a first nitriding treatment step of nitriding the spheroidal graphite cast iron member in a nitriding gas atmosphere having a first nitriding potential; A second nitriding process step of further nitriding the spheroidal graphite cast iron member in a nitriding gas atmosphere having a second nitriding potential lower than the first nitriding potential after the first nitriding process step, The first nitriding step is carried out at a temperature of 500° C. to 600° C., The second nitriding step is also carried out at a temperature of 500° C. to 600° C., the second nitriding potential is a value within a range of 0.5 to 3.0; The duration of the first nitriding step is longer than the duration of the second nitriding step. A method for producing a spheroidal graphite cast iron member comprising the steps of:
